Russian Federation : Staff Report for the 2016 Article IV Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report, 2016)
This 2016 Article IV Consultation highlights that the Russian economy contracted by 3.7 percent in 2015 owing to falling oil prices and the quasi closure of international financial markets to Russian entities. The economic contraction is nonetheless shallower than previous recessions as a stronger external position and the authorities' economic package cushioned the shocks, helped restore confidence and stabilized the financial system. Lower oil prices and needed fiscal adjustment will keep the economy in recession in 2016 with an expected decline in real GDP of 1.2 percent. Growth is expected to resume in 2017 and reach 1 percent, as domestic demand slowly recovers on the back of easing financial conditions and pent up demand.